Prevalence and Determinants of Mental Health Problems and Mental Health Stigma Among Medical Students of Different Nationalities in Qatar - Mahgoub Y; Daher-Nashif S; Al-Shebly R; Wali HS; Khan A; Almarkhi A; Al-Motawa M; AlObaidan G; Al-Muhannadi Z (Advances in Medical Education and Practice, 2022)
Yasmine Mahgoub,1 Suhad Daher-Nashif,2 Rafal Al-Shebly,1 Hamza Said Wali,1 Aisha Khan,1 Ameera Almarkhi,1 Maryam Al-Motawa,1 Ghalya AlObaidan,1 Zamzam Al-Muhannadi1 1College of Medicine, QU Health, Qatar University, Doha, Qatar; 2Population Medicine Department, College of Medicine, QU Health, Qatar University, Doha, QatarCorrespondence: Suhad Daher-Nashif, Population Medicine Department, College of Medicine, QU Health, Qatar University, Doha, Qatar, Email snashif@qu.edu.qa; suhadh@hotmail.comIntroduction: Past studies have shown high prevalence of mental illness among medical students. This is often linked to the demands of the medical curriculum, and to mental health stigma that prevents students from seeking help. This study aimed to examine experiences of mental health problems among medical students of different nationalities in Qatar and to uncover sociodemographic factors related to their prevalence and associated stigma.Methods: A cross-sectional online survey was conducted with medical students in their second through fifth years at the College of Medicine at Qatar University. The survey began with a consent form, and those agreed to take the survey were directed to the questionnaire. The survey comprised 64 items across three sections. The first section collected sociodemographic data. The second section screened depressive symptoms using the PHQ-9; anxiety symptoms using GAD-7; and psychological distress symptoms using Kessler-6. The third section included 27 questions adopted from Schwenk et al, which evaluate students’ perceptions of stigma and their attitudes toward seeking help with their mental health.Results: One hundred and eighty-two students participated in the study. The prevalence of self-reported symptoms of severe depression, anxiety, and psychological distress was 4.4% (95% CI 2– 9), 10.4% (95% CI 7– 16), and 39.6% (95% CI 33– 47), respectively; the prevalence of high stigma was 31.9% (95% CI 25– 39). Parental education, repetition of an academic year, progress in medical studies, gender, and nationality had statistically significant correlations with mental health problems and stigma.Conclusion: In addition to the impact of the requirements of medical study, the high prevalence of reported mental illness among medical students is impacted by sociodemographic factors and the mental health stigma that constitutes a barrier to seeking help. Preventive wellbeing programs should be an essential component of medical curricula.Keywords: mental health problems, mental health stigma, medical students, problem based learning curriculum, sociodemographic factors, Middle East